Curable adhesive composition and polarizing plate
Patent Information
- Application Number
- KR1020237024907
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-12-17
- Filing Date
- 2021-12-24
- Publication Date
- 2026-09-01
- Estimated Expiration
- 2041-12-24
Smart Images

Figure 112023080049998-PCT00007_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a curable adhesive composition and a polarizing plate. Background Technology
[0002] Polarizers, which are widely used in image display devices such as liquid crystal displays and organic EL displays, typically have a configuration in which a thermoplastic resin film, such as a protective film, is bonded to one or both sides of a polarizer. An adhesive is typically used for bonding the polarizer and the thermoplastic resin film. As such adhesives, active energy beam curable adhesives or water-based adhesives are known [e.g., Japanese Patent Publication No. 2009-008860 (Patent Document 1)]. Prior art literature
[0003] Patent Document 1: Japanese Patent Publication No. 2009-008860 The problem to be solved
[0004] The object of the present invention is to provide a curable adhesive composition suitable for bonding a polarizer and a thermoplastic resin film. Another object of the present invention is to provide a polarizing plate comprising a polarizer, an adhesive layer, and a thermoplastic resin film in this order, wherein the polarizer and the thermoplastic resin film have good adhesion. means of solving the problem
[0005] The present invention provides a curable adhesive composition and a polarizing plate as described below.
[0006] [1] A curable adhesive composition comprising a maleic anhydride modified compound (A), an unmodified polybutadiene (B), a (meth)acrylate compound (C) and a photopolymerization initiator (D).
[0007] [2] A curable adhesive composition described in [1] in which the content of the maleic anhydride modified compound (A) is 40 mass% or more and 90 mass% or less of the total amount of the maleic anhydride modified compound (A) and unmodified polybutadiene (B) in 100 mass%.
[0008] [3] The above (meth)acrylate compound (C) is a curable adhesive composition described in [1] or [2] containing a monofunctional (meth)acrylate compound (C-1).
[0009] [4] A curable adhesive composition described in [3] in which the content of the above-mentioned single-function (meth)acrylate compound (C-1) is 60 mass% or more and 99 mass% or less of the above-mentioned (meth)acrylate compound (C) in 100 mass% of the above-mentioned (meth)acrylate compound (C).
[0010] [5] The above single-function (meth)acrylate compound (C-1) comprises at least one compound selected from the group consisting of alicyclic alkyl (meth)acrylate compounds and aromatic (meth)acrylate compounds, in the curable adhesive composition described in [3] or [4].
[0011] [6] A curable adhesive composition described in any one of [1] to [5], further comprising petroleum resin (E).
[0012] [7] The above maleic anhydride modified compound (A) is a curable adhesive composition described in any one of [1] to [6], comprising a maleic anhydride modified polymer (A-1).
[0013] [8] A cured film with a thickness of 10 μm made of the above curable adhesive composition has a moisture permeability of 400 g / (m²·24 hr) or less at a temperature of 40°C and a relative humidity of 90%. [1] to [7] is a curable adhesive composition.
[0014] [9] A polarizing plate comprising a polarizer, an adhesive layer and a thermoplastic resin film in this order,
[0015] The above adhesive layer is a polarizing plate that is a cured layer of a curable adhesive composition described in any one of [1] to [8].
[0016]
[10] The above thermoplastic resin film is a (meth)acrylic resin film, a polarizing plate as described in [9]. Effects of the invention
[0017] A curable adhesive composition suitable for bonding a polarizer and a thermoplastic resin film, and a polarizer comprising a polarizer, an adhesive layer, and a thermoplastic resin film in this order, can provide a polarizer having good adhesion between the polarizer and the thermoplastic resin film. Brief explanation of the drawing
[0018] FIG. 1 is a schematic cross-sectional view showing an example of the layer configuration of a polarizing plate according to the present invention. FIG. 2 is a schematic cross-sectional view showing another example of the layer configuration of a polarizer according to the present invention. Specific details for implementing the invention
[0019] Curable adhesive composition
[0020] The curable adhesive composition according to the present invention (hereinafter also referred to as the "adhesive composition") is suitable for bonding thermoplastic resin films and can be used, for example, for bonding a thermoplastic resin film with another thermoplastic resin film (or layer). One example of application of the adhesive composition according to the present invention is for polarizers, that is, it can be used to manufacture polarizers. More specifically, the adhesive composition according to the present invention is useful as an adhesive composition used for bonding a polarizer and a thermoplastic resin film.
[0021] In this specification, the term "polarizing plate" refers to a laminated optical film comprising a polarizer and a thermoplastic resin film laminated on one or both sides thereof. In the polarizing plate, the polarizer and the thermoplastic resin film are laminated through an adhesive layer. The adhesive layer is a layer formed from an adhesive composition, and more specifically, a cured layer of the adhesive composition.
[0022] The polarizing plate may include a polarizer and a film or layer other than the thermoplastic resin film.
[0023] The adhesive composition above is a curable adhesive composition comprising a maleic anhydride modified compound (A), an unmodified polybutadiene (B), a (meth)acrylate compound (C), and a photopolymerization initiator (D). The adhesive composition may also include components other than these.
[0024] Additionally, the compounds exemplified as each component included or potentially included in the adhesive composition in this specification may be used alone or in combination of multiple types, unless specifically stated otherwise.
[0025] [1] Maleic anhydride modified compound (A)
[0026] The maleic anhydride modified compound (A) is a compound that contains a maleic anhydride structure within its molecule. The adhesive composition may contain one maleic anhydride modified compound (A) or two or more maleic anhydride modified compounds (A).
[0027] As a maleic anhydride modified compound (A), a maleic anhydride modified polymer (A-1) can be cited.
[0028] The maleic anhydride modified polymer (A-1) is a polymer modified by introducing a maleic anhydride structure as a side chain of the polymer. The adhesive composition may contain one type of maleic anhydride modified polymer (A-1) or two or more types of maleic anhydride modified polymers (A-1).
[0029] The above maleic anhydride structure refers to the following structure.
[0030]
[0031] (* indicates a bond loss to the main chain.)
[0032] In the maleic anhydride modified polymer (A-1), the polymer modified by maleic anhydride may be a diene polymer, a polyolefin polymer, a (meth)acrylic polymer, a polyester polymer, a polystyrene polymer, a polyether polymer, etc. These polymers may be homopolymers composed of one type of monomer, or copolymers composed of two or more types of monomers.
[0033] In this specification, "(meth)acrylic" refers to at least one selected from the group consisting of acrylic and methacrylic. The same applies to notations such as "(meth)acryloyl" and "(meth)acrylate".
[0034] The maleic anhydride-modified polymer (A-1) is preferably a maleic anhydride-modified polybutadiene. Each of these polymers may be a homopolymer or a copolymer. In the case of a copolymer, the copolymer monomer is, for example, an olefin monomer.
[0035] Polybutadiene may be 1,4-polybutadiene or 1,2-polybutadiene, and may include both constituent units formed by 1,4-addition and constituent units formed by 1,2-addition. The 1,4-addition may be trans-addition or cis-addition.
[0036] In order to prepare an adhesive composition that is solvent-free and has good adhesive ability, the maleic anhydride modified polymer (A-1) is preferably in liquid form. Liquid form means that it exhibits fluidity at a temperature of 25°C.
[0037] The viscosity of the liquid maleic anhydride modified polymer (A-1) at 25°C is, from the perspective of obtaining an adhesive composition with good coating properties, typically 1 Pa·sec or more and 1300 Pa·sec or less, preferably 10 Pa·sec or more and 1000 Pa·sec or less, more preferably 15 Pa·sec or more and 700 Pa·sec or less, and even more preferably 15 Pa·sec or more and 150 Pa·sec or less.
[0038] The number average molecular weight of the maleic anhydride modified polymer (A-1) is typically 500 or more and 15000 or less, and in terms of viscosity and porosity, preferably 600 or more and 12000 or less, more preferably 700 or more and 10000 or less, and even more preferably 2000 or more and 10000 or less.
[0039] The number average molecular weight of the maleic anhydride modified polymer (A-1) can be measured as a standard polystyrene equivalent value by gel permeation chromatography (GPC).
[0040] The acid value of the maleic anhydride modified polymer (A-1) is typically 10 KOH mg / g or more and 200 KOH mg / g or less, and in terms of the adhesion ability of the adhesive composition to the thermoplastic resin film (or layer), it is preferably 15 KOH mg / g or more and 150 KOH mg / g or less, more preferably 20 KOH mg / g or more and 100 KOH mg / g or less, and even more preferably 45 KOH mg / g or more and 80 KOH mg / g or less. Using the maleic anhydride modified polymer (A-1) having an acid value in the above range is advantageous for increasing the adhesion ability of the adhesive composition to the thermoplastic resin film (or layer), and in particular, when using a polyvinyl alcohol-based polarizer as a polarizer, it is advantageous for providing an adhesive composition with high adhesion between the polyvinyl alcohol-based polarizer and the thermoplastic resin film.
[0041] The acid value of the maleic anhydride modified polymer (A-1) is measured by a neutralization titration method using phenolphthalein as an indicator according to JIS K 0070: 1992.
[0042] When the total amount of the adhesive composition is 100 mass%, the content of the maleic anhydride modified compound (A) is typically 3 mass% or more and 40 mass% or less, and in terms of the adhesion ability of the adhesive composition to the thermoplastic resin film (or layer), particularly in the case where a polyvinyl alcohol-based polarizer is used as a polarizer, in terms of increasing the adhesion between the polyvinyl alcohol-based polarizer and the thermoplastic resin film, it is preferably 5 mass% or more and 35 mass% or less, and more preferably 10 mass% or more and 30 mass% or less.
[0043] [2] Unmodified polybutadiene (B)
[0044] Unmodified polybutadiene (B) is an unmodified polybutadiene and is a polymer obtained by the addition polymerization of 1,3-butadiene. Being unmodified means that it does not contain reactive groups or polar groups in its side chains. The adhesive composition may contain one type of unmodified polybutadiene or two or more types of unmodified polybutadiene.
[0045] The unmodified polybutadiene (B) may be 1,4-polybutadiene or 1,2-polybutadiene, and may include both a constituent unit formed by 1,4-addition (1,4-addition unit) and a constituent unit formed by 1,2-addition (1,2-addition unit). The 1,4-addition may be trans-addition or cis-addition.
[0046] When the unmodified polybutadiene (B) contains both 1,4-addition units and 1,2-addition units, the content of these is in a molar ratio, typically 1,4-addition unit / 1,2-addition unit = 50-95 / 50-5, preferably 70-90 / 30-10, and more preferably 75-90 / 25-10.
[0047] The proportion of vinyl groups included in the unmodified polybutadiene (B) is preferably 35% or less, more preferably 30% or less, more preferably 1% or more, and more preferably 10% or more.
[0048] In order to prepare an adhesive composition that is solvent-free and has good adhesive ability, it is preferable that the unmodified polybutadiene (B) be in liquid form. Liquid form means that it exhibits fluidity at a temperature of 25°C.
[0049] The viscosity of the liquid-type unmodified polybutadiene (B) at 25°C is preferably 0.1 Pa·sec or more and 100 Pa·sec or less, more preferably 0.2 Pa·sec or more and 50 Pa·sec or less, and also preferably 0.5 Pa·sec or more and 10 Pa·sec or less, from the perspective of obtaining an adhesive composition with good coating properties.
[0050] The number average molecular weight of the unmodified polybutadiene (B) is typically 500 or more and 15000 or less, and in terms of viscosity and coating properties, preferably 600 or more and 10000 or less, more preferably 700 or more and 9000 or less, and even more preferably 1000 or more and 5000 or less.
[0051] The number average molecular weight of unmodified polybutadiene (B) can be measured as a standard polystyrene equivalent value by GPC.
[0052] When the total amount of the adhesive composition is 100 mass%, the content of unmodified polybutadiene (B) is typically 1 mass% or more and 20 mass% or less, and in terms of the adhesion ability of the adhesive composition to a thermoplastic resin film (or layer), particularly in the case where a polyvinyl alcohol-based polarizer is used as a polarizer, in terms of increasing the adhesion between the polyvinyl alcohol-based polarizer and the thermoplastic resin film, it is preferably 2 mass% or more and 18 mass% or less, and more preferably 3 mass% or more and 15 mass% or less.
[0053] When the total amount of the adhesive composition is 100 mass%, the total amount of the maleic anhydride modified compound (A) and the unmodified polybutadiene (B) is typically 4 mass% or more and 60 mass% or less, and in terms of the adhesive ability of the adhesive composition to the thermoplastic resin film (or layer), particularly in the case where a polyvinyl alcohol-based polarizer is used as a polarizer, in terms of increasing the adhesion between the polyvinyl alcohol-based polarizer and the thermoplastic resin film, it is preferably 5 mass% or more and 50 mass% or less, more preferably 10 mass% or more and 40 mass% or less, and even more preferably 15 mass% or more and 30 mass% or less.
[0054] When the total amount of maleic anhydride modified compound (A) and unmodified polybutadiene (B) in the adhesive composition is 100 mass%, the content of unmodified polybutadiene (B) is typically 5 mass% or more and 65 mass% or less, and in terms of the adhesive ability of the adhesive composition to a thermoplastic resin film (or layer), particularly in the case where a polyvinyl alcohol-based polarizer is used as a polarizer, in terms of increasing the adhesion between the polyvinyl alcohol-based polarizer and the thermoplastic resin film, it is preferably 10 mass% or more and 60 mass% or less, and more preferably 20 mass% or more and 50 mass% or less.
[0055] When the total amount of maleic anhydride modified compound (A) and unmodified polybutadiene (B) in the adhesive composition is 100 mass%, the content of the maleic anhydride modified compound (A) is preferably 40 mass% or more and 90 mass% or less, and more preferably 50 mass% or more and 80 mass% or less, in terms of the adhesion ability of the adhesive composition to the thermoplastic resin film (or layer), particularly in terms of increasing the adhesion between the polyvinyl alcohol-based polarizer and the thermoplastic resin film when a polyvinyl alcohol-based polarizer is used as a polarizer.
[0056] [3] (Met)acrylate compound (C)
[0057] (Met)acrylate compound (C) is a radical polymerizable compound having one or more (meth)acryloyloxy groups in the molecule.
[0058] The adhesive composition may contain one or more (meth)acrylate compounds (C).
[0059] Examples of (meth)acrylate compounds (C) include monofunctional (meth)acrylate compounds (C-1) having one (meth)acryloyloxy group in the molecule, difunctional (meth)acrylate compounds (C-2) having two (meth)acryloyloxy groups in the molecule, and polyfunctional (meth)acrylate compounds (C-3) having three or more (meth)acryloyloxy groups in the molecule.
[0060] The (meth)acrylate compound (C) may contain one or more types of a monofunctional (meth)acrylate compound (C-1), a difunctional (meth)acrylate compound (C-2), and a polyfunctional (meth)acrylate compound (C-3), each.
[0061] An example of a monofunctional (meth)acrylate compound (C-1) is an alkyl (meth)acrylate. Examples of alkyl (meth)acrylates include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, i-propyl (meth)acrylate, n-butyl (meth)acrylate, i-butyl (meth)acrylate, t-butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, etc.
[0062] Other examples of monofunctional (meth)acrylate compounds (C-1) include, for instance,
[0063] Aromatic (meth)acrylate compounds comprising a group of aromatic rings bonded to the -O- of an ester bond (-C(=O)-O-), such as aracleyl (meth)acrylates including benzyl (meth)acrylate, and phenoxy(meth)acrylates including 2-phenoxyethyl (meth)acrylate, phenoxyethylene glycol (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, ethoxylated-o-phenylphenol (meth)acrylate, etc.;
[0064] Alicyclic alkyl (meth)acrylate compounds comprising a group having an alicyclic ring bonded to the -O- of an ester bond (-C(=O)-O-), such as cyclohexyl (meth)acrylate, cyclohexylmethyl (meth)acrylate, dicyclofentanyl (meth)acrylate, 1,4-cyclohexanedimethanol mono(meth)acrylate), isobornyl (meth)acrylate, etc.
[0065] Aminoalkyl (meth)acrylate compounds such as N,N-dimethylaminoethyl (meth)acrylate;
[0066] Examples of (meth)acrylate compounds include dicyclopentenyloxyethyl (meth)acrylate, ethyl carbitol (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, etc., in which the group bonded to the -O- of the ester bond (-C(=O)-O-) contains an ether bond, and other compounds may be included.
[0067] Another example of a monofunctional (meth)acrylate compound (C-1) is, for instance,
[0068] (Meth)acrylate compounds comprising a hydroxyl group that is bonded to the -O- of an ester bond (-C(=O)-O-), such as 2-hydroxyethyl (meth)acrylate, 2- or 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, trimethylolpropane mono(meth)acrylate, pentaerythritol mono(meth)acrylate, etc.
[0069] Examples include (meth)acrylate compounds in which the group bonded to the -O- of an ester bond (-C(=O)-O-) contains a carboxyl group, such as 2-carboxyethyl (meth)acrylate, ω-carboxy-polycaprolactone (n≒2) mono(meth)acrylate, 1-[2-(meth)acryloyloxyethyl]phthalic acid, 1-[2-(meth)acryloyloxyethyl]hexahydrophthalic acid, 1-[2-(meth)acryloyloxyethyl]succinic acid, 4-[2-(meth)acryloyloxyethyl]trimellitic acid, N-(meth)acryloyloxy-N',N'-dicarboxymethyl-p-phenylenediamine.
[0070] Examples of 2-function (meth)acrylate compounds (C-2) include alkylene glycol di(meth)acrylate, polyoxyalkylene glycol di(meth)acrylate, halogen-substituted alkylene glycol di(meth)acrylate, di(meth)acrylate of aliphatic polyol, di(meth)acrylate of hydrogenated dicyclopentadiene or tricyclodecanedialkanol, di(meth)acrylate of dioxane glycol or dioxanedialkanol, di(meth)acrylate of alkylene oxide adduct of bisphenol A or bisphenol F, epoxy di(meth)acrylate of bisphenol A or bisphenol F, etc.
[0071] More specific examples of 2-function (meth)acrylate compounds (C-2) include ethylene glycol di(meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, trimethylolpropane di(meth)acrylate, pentaerythritol di(meth)acrylate, ditrimethylolpropane di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, tripropylene glycol di(meth)acrylate, polyethylene glycol di(meth)acrylate, and polypropylene glycol di(meth)acrylate. Polytetramethylene glycol di(meth)acrylate, silicon di(meth)acrylate, di(meth)acrylate of hydroxypivalsan neopentyl glycol ester, 2,2-bis[4-(meth)acryloyloxyethoxyethoxyphenyl]propane, 2,2-bis[4-(meth)acryloyloxyethoxyethoxycyclohexyl]propane, hydrogenated dicyclopentadienyl di(meth)acrylate, tricyclodecanedimethanol di(meth)acrylate, 1,3-dioxane-2,5-diyl di(meth)acrylate [alias: dioxane glycol di(meth)acrylate], acetal compound of hydroxypivalaldehyde and trimethylolpropane [chemical name: These include di(meth)acrylate of 2-(2-hydroxy-1,1-dimethylethyl)-5-ethyl-5-hydroxymethyl-1,3-dioxane), tris(hydroxyethyl)isocyanurate di(meth)acrylate, di(meth)acrylate of ethoxylated bisphenol A, di(meth)acrylate of propoxylated bisphenol A, di(meth)acrylate of ethoxylated bisphenol F, di(meth)acrylate of propoxylated bisphenol F, etc.
[0072] The 2-function (meth)acrylate (C-2) preferably has at least one alicyclic backbone or, at least one aromatic ring within the molecule, and more preferably has at least one aromatic ring.
[0073] The 2-function (meth)acrylate (C-2) is preferably a compound represented by the following formula, and more preferably a compound represented by the following formula, in terms of moisture permeability of the cured product, compatibility with maleic anhydride modified compound (A), and adhesion to a thermoplastic resin film (especially a (meth)acrylic resin film).
[0074]
[0075] (In the formula, R1 and R2 each independently represent a hydrogen atom or a methyl group, X represents ethylene oxide (-C2H4O-) or propylene oxide (-C3H6O-), n represents an integer from 1 to 20, and m represents an integer from 1 to 20.)
[0076] X is preferably ethylene oxide, and the average of the sum of m and n is preferably 2 to 20, more preferably 3 to 15, and even more preferably 4 to 13.
[0077] As a polyfunctional (meth)acrylate compound (C-3) having three or more (meth)acryloyloxy groups in the molecule, the poly(meth)acrylate of an aliphatic polyol with three or more functions, such as glycerin tri(meth)acrylate, alkoxylated glycerin tri(meth)acrylate, trimethylolpropane tri(meth)acrylate, ditrimethylolpropane tri(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol tetra(meth)acrylate, dipentaerythritol penta(meth)acrylate, dipentaerythritol hexa(meth)acrylate;
[0078] Poly(meth)acrylate of a halogen-substituted polyol with three or more functions;
[0079] Tri(meth)acrylate of an alkylene oxide adduct of glycerin;
[0080] Tri(meth)acrylate of an alkylene oxide adduct of trimethylolpropane;
[0081] 1,1,1-Tris[(meth)acryloyloxyethoxyethoxy]propane;
[0082] Examples include tris(hydroxyethyl)isocyanurate and tri(meth)acrylate.
[0083] In terms of reducing the viscosity of the adhesive composition and the adhesive ability of the adhesive composition to a thermoplastic resin film (or layer), it is preferable that the (meth)acrylate compound (C) comprises a monofunctional (meth)acrylate compound (C-1).
[0084] In terms of reducing the viscosity of the adhesive composition and the adhesive ability of the adhesive composition to a thermoplastic resin film (or layer), the monofunctional (meth)acrylate compound (C-1) preferably comprises at least one compound selected from the group consisting of alicyclic alkyl (meth)acrylate compounds and aromatic (meth)acrylate compounds.
[0085] When the total amount of the adhesive composition is 100 mass%, the content of the (meth)acrylate compound (C) is typically 15 mass% or more and 75 mass% or less, and in terms of the adhesive ability of the adhesive composition to a thermoplastic resin film (or layer), it is preferably 15 mass% or more and 70 mass% or less, and more preferably 20 mass% or more and 60 mass% or less.
[0086] When the total amount of (meth)acrylate compound (C) is 100 mass%, the content of the monofunctional (meth)acrylate compound (C-1) is typically 60 mass% or more, and in terms of the adhesive ability of the adhesive composition to the thermoplastic resin film (or layer), it is preferably 70 mass% or more, and more preferably 80 mass% or more.
[0087] When the total amount of (meth)acrylate compound (C) is 100 mass%, the content of the single-function (meth)acrylate compound (C-1) may be 100 mass%, but from the perspective of the mechanical strength of the cured product of the adhesive composition, and furthermore, the mechanical strength of the polarizer produced using the adhesive composition, it is preferably 99 mass% or less, more preferably 98 mass% or less, and may be 90 mass% or less.
[0088] When the content of the monofunctional (meth)acrylate compound (C-1) is less than 100 mass%, the remainder of the (meth)acrylate compound (C) is a difunctional (meth)acrylate compound (C-2) and / or a polyfunctional (meth)acrylate compound (C-3), preferably comprising the difunctional (meth)acrylate compound (C-2).
[0089] [4] Photopolymerization initiator (D)
[0090] The photopolymerization initiator (D) is not particularly limited as long as it is a compound capable of generating active radicals, acids, etc., by the action of light to initiate the polymerization of the (meth)acrylate compound (C).
[0091] The adhesive composition may include only one type of photopolymerization initiator (D), or may include two or more types.
[0092] As for the photopolymerization initiator (D), examples include oxime-based compounds such as O-acyloxime compounds, alkylphenone compounds, acylphosphine oxide compounds, etc., although not particularly limited.
[0093] O-acyloxime compounds are compounds having a structure represented by the following formula (d). Hereinafter, * indicates a bond loss.
[0094]
[0095] As O-acyloxime compounds, N-benzoyloxy-1-(4-phenylsulfanylphenyl)butan-1-one-2-imine, N-benzoyloxy-1-(4-phenylsulfanylphenyl)octan-1-one-2-imine, N-benzoyloxy-1-(4-phenylsulfanylphenyl)-3-cyclopentylpropan-1-one-2-imine, N-acetoxy-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]ethane-1-imine, N-acetoxy-1-[9-ethyl-6-{2-methyl-4-(3,3-dimethyl-2,4-dioxacyclofentanylmethyloxy)benzoyl}-9H-carbazole-3-yl]ethane-1-imine, Examples include N-acetoxy-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-3-cyclopentylpropane-1-imine, N-benzoyloxy-1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazole-3-yl]-3-cyclopentylpropane-1-one-2-imine, N-acetyloxy-1-[4-(2-hydroxyethyloxy)phenylsulfanylphenyl]propane-1-one-2-imine, N-acetyloxy-1-[4-(1-methyl-2-methoxyethoxy)-2-methylphenyl]-1-(9-ethyl-6-nitro-9H-carbazole-3-yl)methane-1-imine.
[0096] You may use commercially available products such as Iga Cure (product name) OXE01, OXE02, OXE03 (all manufactured by BASF), N-1919, NCI-930, NCI-831 (all manufactured by ADEKA).
[0097] The alkylphenone compound is a compound having a partial structure represented by the following formula (d4) or a partial structure represented by the following formula (d5). Among these partial structures, the benzene ring may have a substituent.
[0098]
[0099] Examples of compounds having the structure represented by formula (d4) include 2-methyl-2-morpholino-1-(4-methylsulfanylphenyl)propan-1-one, 2-dimethylamino-1-(4-morpholinophenyl)-2-benzylbutan-1-one, 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinophenyl)phenyl]butan-1-one.
[0100] You may use commercially available products such as Omnirad (product name) 369, 907, and 379 (all manufactured by IGM Resins BV).
[0101] Examples of compounds having the structure represented by formula (d5) include 2-hydroxy-2-methyl-1-phenylpropan-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexylphenylketone, oligomer of 2-hydroxy-2-methyl-1-(4-isopropenphenylphenyl)propan-1-one, α,α-diethoxyacetophenone, benzyldimethylketal, etc.
[0102] You may use commercially available products such as Omnirad (product name) 184 (manufactured by IGM Resins BV).
[0103] Examples of acylphosphine oxide compounds include phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (e.g., trade name “Omnirad 819” (manufactured by IGM Resins BV)), 2,4,6-trimethylbenzoyldiphenylphosphine oxide, etc.
[0104] Additional examples of photopolymerization initiators (D) include:
[0105] Benzoin compounds such as benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, benzoin isobutyl ether, etc.;
[0106] Benzophenone compounds such as benzophenone, o-methyl benzoyl benzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, 2,4,6-trimethylbenzophenone, 4,4'-di(N,N'-dimethylamino)-benzophenone;
[0107] Xanthone compounds such as 2-isopropylthioxanthone, 2,4-diethylthioxanthone, etc.;
[0108] Anthracene compounds such as 9,10-dimethoxycyanthracene, 2-ethyl-9,10-dimethoxycyanthracene, 9,10-diethoxycyanthracene, and 2-ethyl-9,10-diethoxycyanthracene;
[0109] Quinone compounds such as 9,10-phenanthrenquinone, 2-ethylanthraquinone, and camphorquinone;
[0110] Examples include benzyl, methyl phenylglyoxylate, titanocene compounds, etc.
[0111] When the total amount of the adhesive composition is 100 mass%, the content of the photopolymerization initiator (D) is typically 0.1 mass% or more and 20 mass% or less, and, in terms of the curability of the adhesive composition and the adhesive ability of the adhesive composition to a thermoplastic resin film (or layer), is preferably 0.5 mass% or more and 15 mass% or less, and more preferably 1 mass% or more and 10 mass% or less (e.g., 8 mass% or less).
[0112] When the total amount of (meth)acrylate compound (C) is 100 parts by mass, the content of photopolymerization initiator (D) is typically 0.1 parts by mass or more and 30 parts by mass or less, and, from the perspective of the curability of the adhesive composition and the adhesive ability of the adhesive composition to a thermoplastic resin film (or layer), is preferably 0.5 parts by mass or more and 20 parts by mass or less, and more preferably 1 part by mass or more and 10 parts by mass or less.
[0113] [5] Tackifier
[0114] The adhesive composition may further include a tackifier. The tackifier resin is not particularly limited and can be appropriately selected from known ones, such as rosin derivatives (e.g., rosin, polymerized rosin, hydrogenated rosin), terpene resins (e.g., terpene resin, aromatic modified terpene resin, terpene phenol resin, hydrogenated terpene resin), petroleum resin, phenolic resin, xylene resin, etc.
[0115] Among these, it is preferable that the adhesive composition further includes petroleum resin (E). By further including petroleum resin (E) in the adhesive composition, adhesion can be improved and moisture permeability of the cured film formed by the adhesive composition can be reduced.
[0116] An adhesive composition capable of forming a low-moisture-permeability cured film is suitable for applications where it is required to suppress the entry and exit of moisture through the cured film. For example, in a polarizing plate or an image display panel comprising the same in which a thermoplastic resin film is laminated through an adhesive layer on at least one side of a polarizer, if the adhesive layer is low-moisture-permeability, it becomes possible to suppress curling (bending) of the polarizing plate or image display panel caused by the entry and exit of moisture.
[0117] The adhesive composition further including petroleum resin (E) may also be advantageous for improving the adhesion between the polarizer and the thermoplastic resin film.
[0118] Examples of petroleum resins (E) include aromatic petroleum resins, aliphatic petroleum resins, cyclic aliphatic petroleum resins, aliphatic and aromatic petroleum resins, coumarone resins, etc. In addition, hydrogenated versions of these resins are also examples.
[0119] The aromatic petroleum resin is a resin containing one or more constituent units derived from aromatic hydrocarbons, and may be a resin that has been hydrogenated or modified.
[0120] The aromatic petroleum resin is preferably a C9-based petroleum resin. The C9-based petroleum resin is a resin obtained by copolymerizing a C9 fraction, and may be a resin to which hydrogen has been added or a modified resin.
[0121] The C9-based petroleum resin may be a resin obtained by copolymerizing a C9 fraction with other monomer components, or it may be a resin that has been hydrogenated or modified. Examples of other monomer components include C5 fractions.
[0122] Examples of C9 fractions include petroleum fractions with 8 to 10 carbon atoms, such as styrene, alkylstyrene, vinyltoluene, 1-methyl-1-phenylethylene, indene, and methylindene.
[0123] Examples of C5 fractions include petroleum fractions with 4 to 5 carbon atoms, such as cyclopentadiene, pentene, pentadiene, isoprene, and piperylene.
[0124] In addition, the petroleum resin (E) may be a C5-based petroleum resin obtained by copolymerizing the aforementioned C5 fraction, a C5-based petroleum resin to which hydrogen has been added, or a modified version of the resin. It may also be an alicyclic hydrocarbon resin obtained by polymerizing the C5 fraction after cyclizing it into a dimer. Examples of alicyclic hydrocarbon resins include polymers containing constituent units derived from dicyclopentadiene.
[0125] The weight average molecular weight of the petroleum resin (E) is typically 500 or more and 10,000 or less, and is preferably 500 or more and 7,000 or less, more preferably 600 or more and 5,000 or less, and even more preferably 600 or more and 3,000 or less, in terms of reducing the moisture permeability of the cured film formed by the adhesive composition and the adhesive ability of the adhesive composition to the thermoplastic resin film (or layer).
[0126] The weight-average molecular weight of the petroleum resin (E) can be measured as a standard polystyrene equivalent value by GPC.
[0127] In the case where the adhesive composition includes petroleum resin (E), when the total amount of the adhesive composition is 100 mass%, the content of the petroleum resin (E) is preferably 20 mass% or more and 70 mass% or less, and more preferably 30 mass% or more and 65 mass% or less, from the perspective of reducing the moisture permeability of the cured film formed by the adhesive composition, and from the perspective of the adhesive ability of the adhesive composition to the thermoplastic resin film (or layer), in particular, from the perspective of increasing the adhesion between the polyvinyl alcohol-based polarizer and the thermoplastic resin film when a polyvinyl alcohol-based polarizer is used as a polarizer.
[0128] It is desirable that the moisture permeability of the cured film formed by the adhesive composition be low. A cured film with a thickness of 10 μm made of the adhesive composition has a moisture permeability measured by the cup method specified in JIS Z 0208 under conditions of a temperature of 40°C and a relative humidity of 90%, which is preferably 400 g / (m²·24 hr) or less, more preferably 300 g / (m²·24 hr) or less, and even more preferably 200 g / (m²·24 hr) or less. The above moisture permeability is typically 1 g / (m²·24 hr) or more, for example 5 g / (m²·24 hr) or more.
[0129] The moisture permeability J of a cured film made of an adhesive composition can be specifically obtained by forming a laminate on a known substrate film to form the cured film, measuring the moisture permeability of the laminate by the above method, and using the measurement results based on the following formula.
[0130] 1 / Jt=(1 / J)+(1 / Jsub)
[0131] In the above formula, Jt is the moisture permeability of the laminate, and Jsub is the moisture permeability of the substrate film. As the substrate film, the same as the thermoplastic resin film described later may be used. When measuring the moisture permeability of the laminate according to JIS Z 0208, the laminate is attached to a cup with the cured film facing outward.
[0132] With respect to the above laminate, when, for example, a (meth)acrylic resin film with a thickness of 60 μm is used as the substrate film, the laminate of the (meth)acrylic resin film and the cured film with a thickness of 10 μm composed of an adhesive composition has a moisture permeability of preferably 55 g / (m²·24 hr) or less, and more preferably 50 g / (m²·24 hr) or less, measured under conditions of a temperature of 40°C and a relative humidity of 90% by the cup method specified in JIS Z 0208. The moisture permeability is typically 1 g / (m²·24 hr) or more, for example 5 g / (m²·24 hr) or more.
[0133] [6] Other components
[0134] The adhesive composition may include other components other than those mentioned above.
[0135] Other components include curable components other than (meth)acrylate compounds (C), crosslinking agents; coupling agents, antioxidants, UV absorbers, heat stabilizers, and other additives.
[0136] [7] Viscosity of the adhesive composition
[0137] The viscosity of the adhesive composition at 25°C is preferably 10,000 mPa·sec or less, more preferably 2 mPa·sec or more and 7,000 mPa·sec or less, and even more preferably 300 mPa·sec or more and 5,000 mPa·sec or less.
[0138] The viscosity of the adhesive composition at 25°C can be measured by an E-type viscometer.
[0139] Polarizer
[0140] The adhesive composition according to the present invention is suitable for bonding thermoplastic resin films and can be used, for example, for bonding a thermoplastic resin film with another thermoplastic resin film (or layer). One example of application of the adhesive composition according to the present invention is for polarizers, that is, it can be used to manufacture polarizers. More specifically, the adhesive composition according to the present invention is useful as an adhesive composition used for bonding thermoplastic resin films, such as a polarizer and a protective film laminated thereon.
[0141] A polarizing plate according to the present invention comprises a polarizer and a thermoplastic resin film laminated on at least one surface thereof through an adhesive layer formed of the adhesive composition. The adhesive layer is a cured layer of the adhesive composition.
[0142] Since the polarizing plate according to the present invention bonds the polarizer and the thermoplastic resin film using the adhesive composition, the adhesion between the polarizer and the thermoplastic resin film can be improved, and the moisture and heat durability of the polarizing plate can also be improved. That is, according to the present invention, it is possible to provide a polarizing plate in which the adhesion between the polarizer and the thermoplastic resin film is good even after being placed in a moisture and heat environment.
[0143] The polarizing plate according to the present invention can be suitably used in image display devices such as liquid crystal display devices and organic EL devices.
[0144] [1] Composition of polarizer
[0145] Examples of the layer configuration of a polarizing plate according to the present invention are shown in FIGS. 1 and FIGS. 2.
[0146] As shown in FIG. 1, the polarizing plate according to the present invention may comprise a polarizer (30), a first adhesive layer (15), and a first thermoplastic resin film (10) in this order, that is, it may comprise a polarizer (30) and a first thermoplastic resin film (10) laminated and bonded to one side thereof through the first adhesive layer (15).
[0147] It is preferable that the first adhesive layer (15) and the first thermoplastic resin film (10) are in direct contact.
[0148] It is preferable that the polarizer (30) and the first adhesive layer (15) are in direct contact.
[0149] In addition, as shown in FIG. 2, the polarizing plate according to the present invention may comprise a polarizer (30), a first thermoplastic resin film (10) laminated and bonded to one side thereof through a first adhesive layer (15), and a second thermoplastic resin film (20) laminated and bonded to the other side thereof through a second adhesive layer (25).
[0150] It is preferable that the first adhesive layer (15) and the first thermoplastic resin film (10) are in direct contact.
[0151] It is preferable that the polarizer (30) and the first adhesive layer (15) are in direct contact.
[0152] It is preferable that the second adhesive layer (25) and the second thermoplastic resin film (20) are in direct contact.
[0153] It is preferable that the polarizer (30) and the second adhesive layer (25) are in direct contact.
[0154] When the polarizing plate has a first adhesive layer (15) and a second adhesive layer (25), either one may be formed of the adhesive composition according to the present invention, or both adhesive layers may be formed of the adhesive composition according to the present invention. The adhesive layer formed of the adhesive composition according to the present invention is preferably the adhesive layer on the viewing side (the adhesive layer far from the adhesive layer described later).
[0155] In the case where both adhesive layers are formed with the adhesive composition according to the present invention, the adhesive compositions may have the same composition or different compositions.
[0156] The polarizer according to the present invention may include other layers (or films) other than those shown in FIGS. 1 and FIGS. 2, not limited to the examples shown above. Other layers may include, for instance, an adhesive layer laminated on the outer surface of the first thermoplastic resin film (10), the second thermoplastic resin film (20), and / or the polarizer (30); a separator film (also called a "release film") laminated on the outer surface of the adhesive layer; a protect film (also called a "surface protection film") laminated on the outer surface of the first thermoplastic resin film (10), the second thermoplastic resin film (20), and / or the polarizer (30); and an optical functional film (or layer) laminated on the outer surface of the first thermoplastic resin film (10), the second thermoplastic resin film (20), and / or the polarizer (30) through an adhesive layer or an adhesive layer.
[0157] [2] Polarizer
[0158] The polarizer (30) is a film having the function of selectively transmitting linear polarization of one direction from natural light. Examples of polarizers (30) include an iodine-based polarizer in which iodine as a dichromatic pigment is adsorbed and oriented on a polyvinyl alcohol-based resin film, a dye-based polarizer in which a dichromatic dye as a dichromatic pigment is adsorbed and oriented on a polyvinyl alcohol-based resin film, and a coating-type polarizer in which a dichromatic dye in a lyotropic liquid crystal state is coated, oriented, and immobilized. These polarizers are called absorption-type polarizers because they selectively transmit linear polarization of one direction from natural light and absorb linear polarization of the other direction.
[0159] The polarizer (30) is not limited to an absorption type polarizer, and may be a reflection type polarizer that selectively transmits linear polarization of one direction from natural light and reflects linear polarization of the other direction, or a scattering type polarizer that scatters linear polarization of the other direction, but an absorption type polarizer is preferred in that it provides excellent visibility when the polarizer is applied to an image display device, etc.
[0160] Among them, the polarizer (30) is more preferably a polyvinyl alcohol-based polarizer composed of a polyvinyl alcohol-based resin, more preferably a polyvinyl alcohol-based polarizer in which a dichromatic pigment such as iodine or a dichromatic dye is adsorbed and oriented on a polyvinyl alcohol-based resin film, and particularly preferably a polyvinyl alcohol-based polarizer in which iodine is adsorbed and oriented on a polyvinyl alcohol-based resin film.
[0161] A polyvinyl alcohol-based polarizer can be manufactured by a conventionally known method using a polyvinyl alcohol-based resin film (or layer).
[0162] The thickness of the polarizer (30) can be 30 μm or less, and preferably 25 μm or less (e.g., 20 μm or less, further 15 μm or less, further 10 μm or less, further 8 μm or less). The thickness of the polarizer (30) is typically 2 μm or more. Making the thickness of the polarizer (30) small is advantageous for thinning the polarizing plate, and furthermore the image display device to which it is applied.
[0163] [3] Thermoplastic resin film
[0164] The first thermoplastic resin film (10) and the second thermoplastic resin film (20) may each be a film comprising a thermoplastic resin having light transparency (preferably optically transparent), such as a polyolefin resin (polyethylene resin, polypropylene resin, etc.), a polycyclic polyolefin resin (norbornene resin, etc.); a cellulose ester resin (triacetylcellulose, diacetylcellulose, etc.); a polyester resin (polycarbonate resin, polyethylene naphthalate, polybutylene terephthalate, etc.); a polycarbonate resin; a (meth)acrylic resin; or a mixture, copolymer, etc.
[0165] The first thermoplastic resin film (10) and the second thermoplastic resin film (20) may each be an unstretched film, or a uniaxially or biaxially stretched film. The biaxial stretching may be simultaneous biaxial stretching in which stretching occurs in two stretching directions simultaneously, or sequential biaxial stretching in which stretching occurs in a second direction different from the first direction after stretching occurs in the first direction.
[0166] The first thermoplastic resin film (10) and / or the second thermoplastic resin film (20) may be a protective film that serves to protect the polarizer (30), or it may be a protective film that also has an optical function such as a phase difference film.
[0167] For example, a film containing the thermoplastic resin can be stretched (uniaxial stretching or biaxial stretching, etc.) or a liquid crystal layer, etc. can be formed on the thermoplastic resin film to obtain a phase difference film with an arbitrary phase difference value.
[0168] The (meth)acrylic resin may be, for example, a polymer having methacrylic acid ester as the main monomer (containing 50 mass% or more), and it is preferable that it be a copolymer in which methacrylic acid ester is copolymerized with other copolymer components.
[0169] In one embodiment, the (meth)acrylic resin comprises methyl methacrylate as a copolymer component, or comprises methyl methacrylate and methyl acrylate.
[0170] Other copolymer components other than methyl acrylate include, for example, methacrylic acid esters other than methyl methacrylate, such as ethyl methacrylate, n-, i- or t-butyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, benzyl methacrylate, 2-ethylhexyl methacrylate, and 2-hydroxyethyl methacrylate;
[0171] Acrylic acid esters such as ethyl acrylate, n-, i- or t-butyl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, 2-ethylhexyl acrylate, 2-hydroxyethyl acrylate;
[0172] Hydroxyalkylacrylic acid esters such as 2-(hydroxymethyl)methyl acrylate, 2-(1-hydroxyethyl)methyl acrylate, 2-(hydroxymethyl)ethyl acrylate, 2-(hydroxymethyl)acrylate n-, i-, or t-butyl acrylate;
[0173] Unsaturated acids such as methacrylic acid and acrylic acid;
[0174] Halogenated styrenes such as chlorostyrene and bromostyrene;
[0175] Substituted styrenes such as vinyltoluene and α-methylstyrene;
[0176] Unsaturated nitriles such as acrylonitrile and methacrylonitrile;
[0177] Unsaturated acid anhydrides such as maleic anhydride and citraconic anhydride;
[0178] Unsaturated imides such as phenylmaleimide and cyclohexylmaleimide;
[0179] Examples of monofunctional monomers include the above.
[0180] The above other monofunctional monomers may be used alone or in combination of two or more types.
[0181] A multifunctional monomer may be used as the other copolymer component mentioned above.
[0182] As a multifunctional monomer, for example, ethylene glycol or its oligomers such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, nonaethylene glycol di(meth)acrylate, tetradecaethylene glycol di(meth)acrylate, etc., in which both terminal hydroxyl groups are esterified with (meth)acrylic acid;
[0183] Propylene glycol or an oligomer with both terminal hydroxyl groups esterified with (meth)acrylic acid;
[0184] A product in which the hydroxyl group of a dihydric alcohol, such as neopentyl glycol di(meth)acrylate, hexanediol di(meth)acrylate, or butanediol di(meth)acrylate, is esterified with (meth)acrylic acid;
[0185] Bisphenol A, an alkylene oxide adduct of bisphenol A, or a halogen-substituent thereof with both terminal hydroxyl groups esterified with (meth)acrylic acid;
[0186] Polyhydric alcohols such as trimethylolpropane and pentaerythritol esterified with (meth)acrylic acid, and ring-opening epoxy groups of glycidyl (meth)acrylate added to the terminal hydroxyl groups of these;
[0187] A dibasic acid such as succinic acid, adipic acid, terephthalic acid, phthalic acid, or their halogen-substituents, or an alkylene oxide adduct thereof, to which a ring-opening epoxy group of glycidyl (meth)acrylate is added;
[0188] Aryl (meth)acrylates; aromatic divinyl compounds such as divinylbenzene;
[0189] You can lift the back.
[0190] Among them, ethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate, and neopentyl glycol dimethacrylate are preferably used.
[0191] The (meth)acrylic resin may be modified by a reaction between functional groups of the copolymer. Examples of the above reactions include the demethylation condensation reaction within the polymer chain between the methyl ester group of (meth)acrylate and the hydroxyl group of 2-(hydroxymethyl)acrylate, and the dehydration condensation reaction within the polymer chain between the carboxyl group of (meth)acrylic acid and the hydroxyl group of 2-(hydroxymethyl)acrylate.
[0192] The glass transition temperature of the (meth)acrylic resin is preferably 80°C or higher and 160°C or lower. The glass transition temperature can be controlled by adjusting the polymerization ratio of the methacrylic acid ester monomer and the acrylic acid ester monomer, the carbon chain length of each ester group and the type of functional group they possess, and the polymerization ratio of the multifunctional monomer to the total monomer.
[0193] As a means to increase the glass transition temperature of (meth)acrylic resins, it is also effective to introduce a ring structure into the main chain of the polymer. The ring structure is preferably a complex ring structure such as a cyclic acid anhydride structure, a cyclic imide structure, and a lactone structure. Specifically, examples include cyclic acid anhydride structures such as glutaric anhydride structures and succinic anhydride structures; cyclic imide structures such as glutarimide structures and succinimide structures; and lactone ring structures such as butyrolactone and valerolactone.
[0194] The greater the content of ring structures in the main chain, the higher the glass transition temperature of the (meth)acrylic resin tends to be.
[0195] Cyclic acid anhydride structures and cyclic imide structures can be introduced by methods such as copolymerizing monomers having cyclic structures, such as maleic anhydride and maleimide; by introducing cyclic acid anhydride structures by dehydration and demethanol condensation reactions after polymerization; or by introducing cyclic imide structures by reacting amino compounds.
[0196] A resin (polymer) having a lactone ring structure can be obtained by a method in which a polymer having hydroxyl groups and ester groups in the polymer chain is prepared, and then the hydroxyl groups and ester groups in the obtained polymer are cyclized and condensed by heating, if necessary, in the presence of a catalyst such as an organic phosphorus compound, to form a lactone ring structure.
[0197] The first thermoplastic resin film (10) and the second thermoplastic resin film (20) may contain additives as needed. Examples of additives include lubricants, anti-blocking agents, heat stabilizers, antioxidants, ultraviolet absorbers, antistatic agents, impact resistance modifiers, surfactants, etc.
[0198] (Met)acrylic resins may contain acrylic rubber particles as an impact modifier from the perspective of film manufacturability or film impact resistance. Acrylic rubber particles are particles that have an elastomer mainly composed of acrylic acid ester as an essential component, and examples include a single-layer structure containing substantially only this elastomer, or a multi-layer structure in which this elastomer is one layer.
[0199] As an example of the above-mentioned elastomer, a cross-linked elastomer can be cited, in which an alkyl acrylate is the main component and other copolymerizable vinyl monomers and crosslinkable monomers are copolymerized therewith.
[0200] As for the alkyl acrylate that is the main component of the elastomer, examples include methyl acrylate, ethyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, etc., which have 1 to 8 carbon atoms in the alkyl group, and alkyl acrylate having 4 or more carbon atoms in the alkyl group is preferably used.
[0201] Other vinyl monomers copolymerizable with the above alkyl acrylate may include compounds having one polymerizable carbon-carbon double bond in the molecule, and more specifically, methacrylic acid esters such as methyl methacrylate; aromatic vinyl compounds such as styrene; vinyl cyanide compounds such as acrylonitrile.
[0202] Examples of the above-mentioned crosslinkable monomers include crosslinkable compounds having at least two polymerizable carbon-carbon double bonds within the molecule, and more specifically, (meth)acrylates of polyhydric alcohols such as ethylene glycol di(meth)acrylate and butanediol di(meth)acrylate; alkenyl esters of (meth)acrylic acid such as allyl (meth)acrylate; and divinylbenzene.
[0203] Preferably, at least one of the first thermoplastic resin film (10) and the second thermoplastic resin film (20) is a film ((meth)acrylic resin film) comprising a (meth)acrylic resin, and the (meth)acrylic resin film is preferably laminated and bonded to a polarizer (30) through an adhesive layer formed of an adhesive composition according to the present invention.
[0204] The adhesive composition according to the present invention can exhibit good adhesion, particularly when the thermoplastic resin film is a (meth)acrylic resin film. Accordingly, the adhesive composition according to the present invention can be suitably used for bonding a polarizer and a (meth)acrylic resin film.
[0205] A (meth)acrylic resin film preferably comprises a (meth)acrylic resin as its resin component.
[0206] The first thermoplastic resin film (10) and the second thermoplastic resin film (20) may be films composed of the same thermoplastic resin or films composed of different thermoplastic resins. The first thermoplastic resin film (10) and the second thermoplastic resin film (20) may be identical or different in terms of thickness, the presence or absence of additives or their types, phase difference characteristics, etc.
[0207] In one embodiment, the first thermoplastic resin film (10) is a (meth)acrylic resin film, and the second thermoplastic resin film (20) is a polyolefin resin film (preferably a cyclic polyolefin resin film), a cellulose ester resin, or a polyester resin film.
[0208] In another embodiment, the first thermoplastic resin film (10) and the second thermoplastic resin film (20) are (meth)acrylic resin films.
[0209] The first thermoplastic resin film (10) and / or the second thermoplastic resin film (20) may have a surface treatment layer (coating layer), such as a hard coat layer, an anti-glare layer, an anti-reflection layer, a light diffusion layer, an antistatic layer, an antifouling layer, or a conductive layer, on its outer surface (the surface opposite to the polarizer (30)).
[0210] The thickness of the first thermoplastic resin film (10) and the second thermoplastic resin film (20) is typically 5 μm or more and 200 μm or less, preferably 10 μm or more and 120 μm or less, more preferably 10 μm or more and 85 μm or less, and even more preferably 15 μm or more and 65 μm or less. The thickness of the first thermoplastic resin film (10) and the second thermoplastic resin film (20) may be 50 μm or less and 40 μm or less. Making the thickness of the first thermoplastic resin film (10) and the second thermoplastic resin film (20) small is advantageous for thinning polarizers, and furthermore, image display devices to which they are applied.
[0211] On the surface to which the adhesive composition of the first thermoplastic resin film (10) and the second thermoplastic resin film (20) is applied, surface modification treatments such as saponification treatment, plasma treatment, corona treatment, and primer treatment may be performed for the purpose of improving adhesion.
[0212] [4] Manufacture of a polarizing plate, and an adhesive layer
[0213] By laminating and bonding a first thermoplastic resin film (10) to one side of a polarizer (30) through a first adhesive layer (15), a polarizing plate with the configuration shown in FIG. 1 can be obtained, and by further laminating and bonding a second thermoplastic resin film (20) to the other side of a polarizer (30) through a second adhesive layer (25), a polarizing plate with the configuration shown in FIG. 2 can be obtained.
[0214] When manufacturing a polarizing plate having both a first thermoplastic resin film (10) and a second thermoplastic resin film (20) (hereinafter collectively referred to simply as "thermoplastic resin film"), these thermoplastic resin films may be laminated and bonded one side at a time in stages, or the thermoplastic resin films on both sides may be laminated and bonded simultaneously.
[0215] In the polarizing plate of the configuration shown in FIG. 1, the first adhesive layer (15) is formed from an adhesive composition according to the present invention. The first adhesive layer (15) is a cured layer of the adhesive composition according to the present invention.
[0216] In the polarizing plate of the configuration shown in FIG. 2, the first adhesive layer (15) and the second adhesive layer (25) are formed such that at least one of them is formed of an adhesive composition according to the present invention. The first adhesive layer (15) and / or the second adhesive layer (25) is a cured layer of the adhesive composition according to the present invention.
[0217] In the polarizing plate of the configuration shown in FIG. 2, the first adhesive layer (15) and the second adhesive layer (25) may be formed such that one of them is formed with an adhesive composition according to the present invention, and the other is formed with a different adhesive composition that is different from the adhesive composition according to the present invention.
[0218] Other adhesive compositions include conventionally known water-based adhesives or active energy beam curable adhesives.
[0219] As water-based adhesives, for example, conventionally known adhesive compositions using polyvinyl alcohol-based resin or urethane resin as the main component can be cited.
[0220] Active energy beam curable adhesive is an adhesive that cures upon irradiation with active energy beams such as ultraviolet rays, visible light, electron beams, and X-rays. When using an active energy beam curable adhesive, the adhesive layer of the polarizer is the cured layer of the said adhesive.
[0221] An active energy beam curable adhesive may be an adhesive containing an epoxy compound that cures by cationic polymerization as a curable component, and preferably, a UV-curable adhesive containing such an epoxy compound as a curable component. An epoxy compound refers to a compound having an average of one or more, preferably two or more, epoxy groups in its molecule. The epoxy compound may be used as a single type or two or more types may be used in combination.
[0222] Examples of epoxy compounds include hydrogenated epoxy compounds (glycidyl ethers of polyols having a hydrocyclic ring) obtained by reacting epichlorohydrin with an alicyclic polyol obtained by hydrogenating the aromatic ring of an aromatic polyol; aliphatic epoxy compounds such as polyglycidyl ethers of aliphatic polyhydric alcohols or their alkylene oxide adducts; and alicyclic epoxy compounds having one or more epoxy groups bonded to a hydrocyclic ring within the molecule.
[0223] The active energy beam curable adhesive may contain a radically polymerizable (meth)acrylic compound as a curable component, instead of or together with the epoxy compound mentioned above. Examples of (meth)acrylic compounds include (meth)acrylate monomers having one or more (meth)acryloyloxy groups in their molecules; and (meth)acrylate oligomers obtained by reacting two or more functional group-containing compounds and having at least two (meth)acryloyloxy groups in their molecules, which contain (meth)acryloyloxy groups.
[0224] When an active energy beam curable adhesive contains an epoxy compound that is cured by cationic polymerization as a curable component, it is preferable to contain a photocationic polymerization initiator. Examples of photocationic polymerization initiators include aromatic diazonium salts; onium salts such as aromatic iodonium salts or aromatic sulfonium salts; and iron-allene complexes.
[0225] When an active energy beam curable adhesive contains a radical polymerizable component such as a (meth)acrylic compound, it is preferable to contain a photoradical polymerization initiator. Examples of photoradical polymerization initiators include acetophenone-based initiators, benzophenone-based initiators, benzoin ether-based initiators, thioxanthone-based initiators, xanthone, fluorenone, camphorquinone, benzaldehyde, anthraquinone, etc.
[0226] The bonding of the polarizer (30) and the thermoplastic resin film may include a process of applying an adhesive composition to the bonding surface of the polarizer (30) and / or the bonding surface of the thermoplastic resin film, or injecting an adhesive composition between the polarizer (30) and the thermoplastic resin film, overlapping the two films through a layer of adhesive composition, and bonding them by pressing from above and below using, for example, a bonding roll.
[0227] Various coating methods, such as a doctor blade, wire bar, die coater, comma coater, and gravure coater, can be used to form the adhesive composition layer. Additionally, a method may be used in which the polarizer (30) and the thermoplastic resin film are continuously supplied such that the bonding surface of both is on the inside, while the adhesive composition is extended during this process.
[0228] Before applying the adhesive composition, on one or both of the bonding surfaces of the polarizer (30) and the thermoplastic resin film, an adhesive facilitation treatment (surface activation treatment) such as saponification treatment, corona discharge treatment, plasma treatment, flame treatment, primer treatment, or anchor coating treatment may be performed.
[0229] When using an active energy beam curable adhesive, the adhesive composition layer is cured by irradiating it with an active energy beam.
[0230] The light source used to irradiate active energy rays should be capable of generating ultraviolet rays, electron beams, X-rays, etc. In particular, a light source having a light emission distribution at a wavelength of 400 nm or less, such as a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, a metal halide lamp, etc., is suitably used.
[0231] The thickness of the adhesive layer formed by the adhesive composition according to the present invention is, for example, 0.1 μm or more and 100 μm or less in a polarizing plate, preferably 0.5 μm or more and 80 μm or less, more preferably 1 μm or more and 60 μm or less, and even more preferably 2 μm or more and 50 μm or less. From the perspective of thinning the polarizing plate, it is also preferable to make the thickness of the adhesive layer 30 μm or less and 20 μm or less.
[0232] The first adhesive layer (15) and the second adhesive layer (25) may have the same thickness or different thickness.
[0233] [5] Other components of the polarizer
[0234] [5-1] Optical Functional Film
[0235] The polarizing plate may be equipped with an optical functional film other than the polarizer (30) to provide a desired optical function, and a suitable example thereof is a phase difference film.
[0236] As described above, the first thermoplastic resin film (10) and / or the second thermoplastic resin film (20) may serve as a phase difference film, but the phase difference film may also be laminated separately from the thermoplastic resin film. In the latter case, the phase difference film may be laminated to the outer surface of the first thermoplastic resin film (10) and / or the second thermoplastic resin film (20) through an adhesive layer or an adhesive layer.
[0237] Examples of phase difference films include a birefringent film composed of a stretched film of a thermoplastic resin having light transparency; a film in which a discotic liquid crystal or a nematic liquid crystal is oriented and fixed; and a liquid crystal layer formed on a substrate film.
[0238] The base film is typically a film containing a thermoplastic resin, and an example of the thermoplastic resin is a cellulose ester-based resin such as triacetylcellulose.
[0239] As a thermoplastic resin for forming a birefringent film, the one described for the first and second thermoplastic resin films (10, 20) can be used.
[0240] Examples of other optical functional films (optical components) that may be included in a polarizer include a light-concentrating plate, a brightness-enhancing film, a reflective layer (reflective film), a semi-transparent reflective layer (semi-transparent reflective film), and a light-diffusing layer (light-diffusing film). These are generally provided when the polarizer is a polarizer positioned on the back side (backlight side) of a liquid crystal cell.
[0241] [5-2] Adhesive layer
[0242] The polarizing plate according to the present invention may include an adhesive layer for bonding it to an image display element such as a liquid crystal cell or an organic EL element, or to another optical member. The adhesive layer may be laminated to the outer surface of a polarizer (30) in the polarizing plate of the configuration shown in FIG. 1, and to the outer surface of a first thermoplastic resin film (10) or a second thermoplastic resin film (20) in the polarizing plate of the configuration shown in FIG. 2.
[0243] As the adhesive used in the adhesive layer, base polymers such as (meth)acrylic resins, silicone resins, polyester resins, polyurethane resins, and polyether resins may be used. Among these, (meth)acrylic adhesives are preferred from the perspective of transparency, adhesive strength, reliability, weather resistance, heat resistance, and reworkability.
[0244] The thickness of the adhesive layer is determined by its adhesive strength, etc., but a range of 1 μm or more and 50 μm or less is suitable, and preferably 2 μm or more and 40 μm or less.
[0245] The polarizing plate may include a separator film laminated on the outer surface of an adhesive layer. The separator film may be a film comprising a polyethylene-based resin such as polyethylene, a polypropylene-based resin such as polypropylene, a polyester-based resin such as polyethylene terephthalate, etc. Among these, a stretched film of polyethylene terephthalate is preferred.
[0246] The adhesive layer may, if necessary, include glass fibers, glass beads, resin beads, fillers including metal powder or other inorganic powders, pigments, colorants, antioxidants, UV absorbers, antistatic agents, etc.
[0247] [5-3] Protect Film
[0248] The polarizing plate according to the present invention may include a protective film for protecting its surface (such as the surface of a thermoplastic resin film or the surface of a polarizer). The protective film is peeled off for each adhesive layer it has after the polarizing plate is bonded to, for example, an image display element or other optical member.
[0249] The protective film is composed of, for example, a substrate film and an adhesive layer laminated thereon. The aforementioned technology is used for the adhesive layer.
[0250] The resin constituting the base film may be a thermoplastic resin such as a polyethylene-based resin like polyethylene, a polypropylene-based resin like polypropylene, a polyester-based resin like polyethylene terephthalate or polyethylene naphthalate, or a polycarbonate-based resin. Preferably, it is a polyester-based resin such as polyethylene terephthalate.
[0251] Examples
[0252] The present invention will be described in more detail below by presenting examples, but the present invention is not limited by these examples. In the examples, % and parts indicating content or usage amount are based on mass unless otherwise noted. The thickness of the film and the adhesive layer (cured film) was measured using a digital micrometer “MH-15M” manufactured by Nikon Inc.
[0253] <Example 1>
[0254] (1) Preparation of a curable adhesive composition
[0255] Curable adhesive composition A was prepared by mixing the components shown in Table 1 in the amounts shown in Table 1. The unit of the amount of each component shown in Table 1 is parts by mass.
[0256] The details of each component shown in Table 1 are as follows.
[0257] (Aa): Maleic anhydride modified liquid polybutadiene (Synthomer trade name “Lithene ultra N4-5000-10MA”, number average molecular weight: 5500, viscosity at 25°C: 25–60 Pa·sec, acid value: 54 KOH mg / g)
[0258] (Ab): Maleic anhydride modified liquid polybutadiene (Synthomer trade name “Lithene ultra N4-B-10MA”, number average molecular weight: 8200, viscosity at 25°C: 60–90 Pa·sec, acid value: 54 KOH mg / g)
[0259] (Ba): Unmodified liquid polybutadiene (trade name "Lithene ultra PM4" manufactured by Synthomer, number average molecular weight: 1500, viscosity at 25°C: 0.7–0.95 Pa·sec)
[0260] (Bb): Unmodified liquid polybutadiene (trade name "Lithene ultra N4-9000" manufactured by Synthomer, number average molecular weight: 9000, viscosity at 25°C: 12–16 Pa·sec)
[0261] (C-1): Dicyclofentanyl acrylate (product name “FA-513AS” manufactured by Hitachi Gasei Co., Ltd.)
[0262] (C-2): Ethoxylated bisphenol A diacrylate (product name “A-BPE-10” manufactured by Shinnakamura Chemical Co., Ltd., EO 10 mol)
[0263] (D): Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (trademark "Omnirad 819" manufactured by IGM Resins BV)
[0264] (E): Petroleum resin (product name “T-REZ HA105” manufactured by JXTG Energy Co., Ltd.), hydrogenated resin (cycloaliphatic saturated hydrocarbon resin with dicyclopentadiene as a monomer component), softening point (nominal value): 104.5℃, weight average molecular weight (nominal value): 610)
[0265] (2) Fabrication of polarizing plates
[0266] Corona treatment was performed on the surface of a polymethyl methacrylate (PMMA) film with a thickness of 60 μm, and the curable adhesive composition A prepared in (1) above was coated on the corona-treated surface using an adhesive coating device. The obtained coating layer and a polyvinyl alcohol-iodine-based polarizer with a thickness of 23 μm were laminated using a nip roll to obtain a polarizer having a PMMA film.
[0267] Next, corona treatment was performed on the surface of a phase difference film with a thickness of 50 μm containing a cyclic polyolefin resin [product name "ZEONOR" manufactured by Nippon Zeon Co., Ltd.], and a curable adhesive composition B prepared as described below was coated onto the corona-treated surface using an adhesive coating device. The obtained coating layer and the polarizer surface of a polarizer having a PMMA film were laminated using a nip roll to obtain a laminate. Ultraviolet light (UVB) having a total integrated light amount (integrated amount of light irradiation intensity in the wavelength range of 320 to 400 nm) of about 200 mJ / ㎠ (measured by a UV Power Puck II manufactured by Fusion UV Co., Ltd.) was irradiated from the phase difference film side of the laminate to cure the layer of curable adhesive composition B and the layer of curable adhesive composition A, thereby producing a polarizer. In addition, the thickness of the cured layer of curable adhesive composition A was about 10 μm, and the thickness of the cured layer of curable adhesive composition B was 2.5 μm.
[0268] Curable adhesive composition B was prepared by adding and mixing 25 parts by mass of 1,4-butanediol diglycidyl ether (product name "EX-214L" manufactured by Nagase Chemtex Co., Ltd.) and 5.6 parts by mass of a photopolymerization initiator (product name "CPI-100P" manufactured by San Apro Co., Ltd.) to 100 parts by mass of 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (product name "Celoxide 2021P" manufactured by Daicel Co., Ltd.).
[0269] <Examples 2–7>
[0270] Curable adhesive composition A was prepared in the same manner as in Example 1, except that the amounts of the ingredients were changed as shown in Table 1. In addition, a polarizing plate was manufactured in the same manner as in Example 1, except that this curable adhesive composition A was used.
[0271] Measurement and Evaluation
[0272] (1) Moisture permeability of the cured film formed by curable adhesive composition A
[0273] Curable adhesive composition A was coated onto a 60 μm thick PMMA film that had undergone corona treatment using an adhesive coating device.
[0274] An untreated polyethylene terephthalate (PET) film was laminated onto a coated layer of curable adhesive composition A and bonded using a nip roll. Subsequently, the adhesive layer was cured by irradiating ultraviolet (UVB) light with a total integrated light intensity (integrated amount of light irradiation intensity in the wavelength range of 320 to 400 nm) of approximately 200 mJ / cm² (measured using a UV Power Puck II manufactured by Fusion UV), thereby obtaining a laminate having a layer composition of PMMA film / cured adhesive layer / PET film. Afterward, the PET film was peeled off to obtain a laminate (sample for moisture permeability measurement) having a layer composition of PMMA film / cured adhesive layer (cured film).
[0275] For the obtained laminate (sample for measuring water vapor permeability), the water vapor permeability [g / (m²·24 hr)] at a temperature of 40°C and a relative humidity of 90% was measured by the cup method specified in JIS Z 0208. In addition, for the measurement, the cured adhesive layer (cured film) of the laminate was placed under environmental conditions of a temperature of 40°C and a relative humidity of 90%. In addition, the laminate was attached to a cup with the cured film facing outward.
[0276] The results are shown in the column "Moisture Permeability of Laminate" in Table 1. The numbers in parentheses represent the thickness of the hardened film of the laminate (unit: μm).
[0277] In addition, using the moisture permeability (Jt) of the obtained laminate, the moisture permeability (J) of the cured film itself at a temperature of 40°C and a relative humidity of 90% was calculated based on the following formula.
[0278] 1 / Jt=(1 / J)+(1 / Jsub)
[0279] The PMMA film with a thickness of 60 μm, which is the base film, had a water vapor permeability (Jsub) of 70 g / (m²·24 hr) measured by the cup method specified in JIS Z 0208 under conditions of a temperature of 40°C and a relative humidity of 90%.
[0280] The results are shown in the column "Moisture Permeability of Cured Film" of Table 1. The numbers in parentheses represent the thickness of the cured film (unit: μm).
[0281] (2) Evaluation of the adhesion between the polarizer and the PMMA film in the polarizer (initial)
[0282] An adhesive layer was formed on the PMMA film side of the obtained polarizer. The polarizer having the obtained adhesive layer was cut to a size of 200 mm in length (parallel to the absorption axis direction of the polarizer) × 25 mm in width, and the adhesive layer was bonded to a glass plate to obtain a laminate. The obtained laminate was used as a test specimen to measure the peel strength between the polarizer and the PMMA film. A cutter blade was inserted between the polarizer and the PMMA film of the test specimen, peeled 30 mm from the end in the longitudinal direction, the peeled part was held by the grip part of the tester, and the lower part of the grip was held by the glass plate. For the test specimen in this state, a peel test was performed at a grip moving speed of 300 mm / min in an atmosphere of 23°C and 55% relative humidity in accordance with JIS K 6854-2: 1999 “Adhesive-Peel Adhesion Strength Test Method-Part 2: 180-Degree Peeling”, and the average peel strength over a length of 170 mm excluding the 30 mm grip portion was calculated and taken as the peel strength between the polarizer and the PMMA film. The results are shown in Table 1. The peel strength was measured after the polarizer was fabricated and placed in an environment of 23°C and 50% RH relative humidity for 24 hours.
[0283] In Table 1, "breakage" means that the PMMA film or polarizer breaks before the film is peeled off due to very high peel strength.
[0284] (3) Evaluation of adhesion between polarizer and PMMA film in a polarizer (after exposure to high temperature and high humidity environment)
[0285] An adhesive layer was formed on the PMMA film side of the obtained polarizer. The polarizer having the obtained adhesive layer was cut to a size of 200 mm in length (parallel to the absorption axis direction of the polarizer) × 25 mm in width, and the adhesive layer was bonded to a glass plate to obtain a laminate. The obtained laminate was placed for 24 hours in a high temperature and high humidity environment of 80°C and 90% RH relative humidity, and then placed for 24 hours in an environment of 23°C and 50% RH relative humidity. After that, a cutter blade was inserted between the polarizer and the PMMA film of the obtained laminate, and 30 mm was peeled off from the end in the longitudinal direction. The peeled part was held by the grip part of the tester, and the lower part of the grip held the glass plate. For the test specimen in this state, a peel test was performed at a grip moving speed of 300 mm / min in an atmosphere of 23°C and 55% relative humidity in accordance with JIS K 6854-2: 1999 “Adhesives - Peel Adhesion Strength Test Method - Part 2: 180-degree Peel”, and the average peel strength over a length of 170 mm excluding the 30 mm grip portion was calculated and taken as the peel strength between the polarizer and the PMMA film. The results are shown in Table 1.
[0286]
[0287] <Example 8>
[0288] (1) Preparation of a curable adhesive composition
[0289] Curable adhesive composition C was prepared by mixing the components shown in Table 2 in the amounts shown in Table 2. The unit of the amount of each component shown in Table 2 is parts by mass.
[0290] The details of each component shown in Table 2 are as follows.
[0291] (Aa): Maleic anhydride modified liquid polybutadiene (Synthomer trade name “Lithene ultra N4-5000-10MA”, number average molecular weight: 5500, viscosity at 25°C: 25–60 Pa·sec, acid value: 54 KOH mg / g)
[0292] (Ac): Maleic anhydride modified liquid polybutadiene (Synthomer trade name "Lithene ultra PM4-7.5MA", number average molecular weight: 1600, viscosity at 25°C: 2–6 Pa·sec, acid value: 40 KOH mg / g)
[0293] (Ba): Unmodified liquid polybutadiene (trade name "Lithene ultra PM4" manufactured by Synthomer, number average molecular weight: 1500, viscosity at 25°C: 0.7–0.95 Pa·sec)
[0294] (Bb): Unmodified liquid polybutadiene (trade name "Lithene ultra N4-9000" manufactured by Synthomer, number average molecular weight: 9000, viscosity at 25°C: 12–16 Pa·sec)
[0295] (Bc): Unmodified liquid polybutadiene (trade name "Lithene ultra AL" manufactured by Synthomer, number average molecular weight: 700, viscosity at 25°C: 3–5 Pa·sec)
[0296] (C-1): Dicyclofentanyl acrylate (product name “FA-513AS” manufactured by Hitachi Gasei Co., Ltd.)
[0297] (C-2): Ethoxylated bisphenol A diacrylate (product name “A-BPE-10” manufactured by Shinnakamura Chemical Co., Ltd., EO 10 mol)
[0298] (D): Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (trademark "Omnirad 819" manufactured by IGM Resins BV)
[0299] (E): Petroleum resin (product name “T-REZ HA105” manufactured by JXTG Energy Co., Ltd.), hydrogenated resin (cycloaliphatic saturated hydrocarbon resin with dicyclopentadiene as a monomer component), softening point (nominal value): 104.5℃, weight average molecular weight (nominal value): 610)
[0300] (2) Fabrication of polarizing plates
[0301] Corona treatment was performed on the surface of a polymethyl methacrylate (PMMA) film with a thickness of 60 μm, and the curable adhesive composition C prepared in (1) above was coated on the corona-treated surface using an adhesive coating device. The obtained coating layer and a polyvinyl alcohol-iodine-based polarizer with a thickness of 23 μm were laminated using a nip roll to obtain a polarizer having a PMMA film.
[0302] Next, corona treatment was performed on the surface of a phase difference film with a thickness of 50 μm containing a cyclic polyolefin resin [product name "ZEONOR" manufactured by Nippon Zeon Co., Ltd.], and a curable adhesive composition B prepared as described below was coated onto the corona-treated surface using an adhesive coating device. The obtained coating layer and the polarizer surface of a polarizer having a PMMA film were laminated using a nip roll to obtain a laminate. Ultraviolet light (UVB) having a total integrated light amount (integrated amount of light irradiation intensity in the wavelength range of 320 to 400 nm) of approximately 200 mJ / ㎠ (measured by a UV Power Puck II manufactured by Fusion UV Co., Ltd.) was irradiated from the phase difference film side of the laminate to cure the layer of curable adhesive composition B and the layer of curable adhesive composition C, thereby producing a polarizer. In addition, the thickness of the cured layer of curable adhesive composition C was about 10 μm, and the thickness of the cured layer of curable adhesive composition B was 2.5 μm.
[0303] Curable adhesive composition B was prepared by adding and mixing 25 parts by mass of 1,4-butanediol diglycidyl ether (product name "EX-214L" manufactured by Nagase Chemtex Co., Ltd.) and 5.6 parts by mass of a photopolymerization initiator (product name "CPI-100P" manufactured by San Apro Co., Ltd.) to 100 parts by mass of 3',4'-epoxycyclohexylmethyl 3,4-epoxycyclohexanecarboxylate (product name "Celoxide 2021P" manufactured by Daicel Co., Ltd.).
[0304] <Example 9 and Comparative Example 1>
[0305] Curable adhesive composition C was prepared in the same manner as in Example 8, except that the amounts of the ingredients were changed as shown in Table 2. In addition, a polarizing plate was manufactured in the same manner as in Example 8, except that this curable adhesive composition C was used.
[0306] Measurement and Evaluation
[0307] (1) Moisture permeability of the cured film formed by the curable adhesive composition C
[0308] Curable adhesive composition C was coated onto a 60 μm thick PMMA film that had undergone corona treatment using an adhesive coating device.
[0309] An untreated polyethylene terephthalate (PET) film was laminated onto a coated layer of curable adhesive composition C and bonded using a nip roll. Subsequently, the adhesive layer was cured by irradiating ultraviolet (UVB) light with a total integrated light intensity (integrated amount of light irradiation intensity in the wavelength range of 320 to 400 nm) of approximately 200 mJ / cm² (measured using a UV Power Puck II manufactured by Fusion UV), thereby obtaining a laminate having a layer composition of PMMA film / cured adhesive layer / PET film. Afterward, the PET film was peeled off to obtain a laminate (sample for moisture permeability measurement) having a layer composition of PMMA film / cured adhesive layer (cured film).
[0310] For the obtained laminate (sample for measuring water vapor permeability), the water vapor permeability [g / (m²·24 hr)] at a temperature of 40°C and a relative humidity of 90% was measured by the cup method specified in JIS Z 0208. In addition, for the measurement, the cured adhesive layer (cured film) of the laminate was placed under environmental conditions of a temperature of 40°C and a relative humidity of 90%. In addition, the laminate was attached to a cup with the cured film facing outward.
[0311] The results are shown in the column "Moisture Permeability of Laminate" in Table 2. The numbers in parentheses represent the thickness of the hardened film of the laminate (unit: μm).
[0312] In addition, using the moisture permeability (Jt) of the obtained laminate, the moisture permeability (J) of the cured film itself at a temperature of 40°C and a relative humidity of 90% was calculated based on the following formula.
[0313] 1 / Jt=(1 / J)+(1 / Jsub)
[0314] The PMMA film with a thickness of 60 μm, which is the base film, had a water vapor permeability (Jsub) of 70 g / (m²·24 hr) measured by the cup method specified in JIS Z 0208 under conditions of a temperature of 40°C and a relative humidity of 90%.
[0315] The results are shown in the column "Moisture Permeability of Cured Film" of Table 2. The numbers in parentheses represent the thickness of the cured film (unit: μm).
[0316] (2) Evaluation of the adhesion between the polarizer and the PMMA film in the polarizer (initial)
[0317] An adhesive layer was formed on the PMMA film side of the obtained polarizer. The polarizer having the obtained adhesive layer was cut to a size of 200 mm in length (parallel to the absorption axis direction of the polarizer) × 25 mm in width, and the adhesive layer was bonded to a glass plate to obtain a laminate. The obtained laminate was used as a test specimen to measure the peel strength between the polarizer and the PMMA film. A cutter blade was inserted between the polarizer and the PMMA film of the test specimen, peeled 30 mm from the end in the longitudinal direction, the peeled part was held by the grip part of the tester, and the lower part of the grip was held by the glass plate. For the test specimen in this state, a peel test was performed at a grip moving speed of 300 mm / min in an atmosphere of 23°C and 55% relative humidity in accordance with JIS K 6854-2: 1999 “Adhesive-Peel Adhesion Strength Test Method-Part 2: 180-Degree Peeling”, and the average peel strength over a length of 170 mm excluding the 30 mm grip portion was calculated and taken as the peel strength between the polarizer and the PMMA film. The results are shown in Table 2. The peel strength was measured after the polarizer was fabricated and left in an environment of 23°C and 50% RH relative humidity for 24 hours.
[0318] In Table 2, "breakage" means that the PMMA film or polarizer breaks before the film is peeled off due to very high peel strength.
[0319] (3) Evaluation of adhesion between polarizer and PMMA film in a polarizer (after exposure to high temperature and high humidity environment)
[0320] An adhesive layer was formed on the PMMA film side of the obtained polarizer. The polarizer having the obtained adhesive layer was cut to a size of 200 mm in length (parallel to the absorption axis direction of the polarizer) × 25 mm in width, and the adhesive layer was bonded to a glass plate to obtain a laminate. The obtained laminate was placed for 24 hours in a high temperature and high humidity environment of 80°C and 90% RH relative humidity, and then placed for 24 hours in an environment of 23°C and 50% RH relative humidity. After that, a cutter blade was inserted between the polarizer and the PMMA film of the obtained laminate, and 30 mm was peeled from the end in the longitudinal direction. The peeled part was held by the grip part of the tester, and the lower part of the grip held the glass plate. For the test specimen in this state, a peel test was performed at a grip moving speed of 300 mm / min in an atmosphere of 23°C and 55% relative humidity, in accordance with JIS K 6854-2: 1999 “Adhesives - Peel Adhesion Strength Test Method - Part 2: 180-degree Peel”, and the average peel strength over a length of 170 mm excluding the 30 mm grip portion was calculated and taken as the peel strength between the polarizer and the PMMA film. The results are shown in Table 2.
[0321] Explanation of the symbols
[0322] 10 first thermoplastic resin film, 15 first adhesive layer, 20 second thermoplastic resin film, 25 second adhesive layer, 30 polarizer.
Claims
Claim 1 A curable adhesive composition comprising a maleic anhydride modified compound (A), an unmodified polybutadiene (B), a (meth)acrylate compound (C), and a photopolymerization initiator (D), wherein the maleic anhydride modified compound (A) is a compound containing a maleic anhydride structure within its molecule, and the content of the maleic anhydride modified compound (A) is 40 mass% or more and 90 mass% or less of the total amount of the maleic anhydride modified compound (A) and the unmodified polybutadiene (B) at 100 mass%. Claim 2 In claim 1, the (meth)acrylate compound (C) is a curable adhesive composition comprising a monofunctional (meth)acrylate compound (C-1). Claim 3 A curable adhesive composition according to claim 2, wherein the content of the single-function (meth)acrylate compound (C-1) is 60 mass% or more and 99 mass% or less of the 100 mass% of the (meth)acrylate compound (C). Claim 4 In paragraph 2, the single-function (meth)acrylate compound (C-1) comprises at least one compound selected from the group consisting of alicyclic alkyl (meth)acrylate compounds and aromatic (meth)acrylate compounds, in a curable adhesive composition. Claim 5 A curable adhesive composition comprising a petroleum resin (E) further comprising, in claim 1 or 2. Claim 6 In claim 1 or 2, the maleic anhydride modified compound (A) is a curable adhesive composition comprising a maleic anhydride modified polymer (A-1). Claim 7 In claim 1 or 2, the cured film having a thickness of 10 μm made of the curable adhesive composition is a curable adhesive composition having a moisture permeability of 400 g / (m²·24 hr) or less at a temperature of 40°C and a relative humidity of 90%. Claim 8 A polarizing plate comprising a polarizer, an adhesive layer, and a thermoplastic resin film in this order, wherein the adhesive layer is a cured layer of a curable adhesive composition as described in claim 1 or 2. Claim 9 In claim 8, the thermoplastic resin film is a polarizing plate that is a (meth)acrylic resin film. Claim 10 delete
Citation Information
Patent Citations
Modified liquid diene rubber, and resin composition containing said modified liquid diene rubber
CN107001490A
Curable resin composition
JP2015105279A
Laminated optical film, manufacturing method for the same and image display device
JP2019056820A
Polymerizable composition, polymer, optical adhesive sheet, image display device, and method for manufacturing image display device
KR1020140119172A